Social barriers as a challenge in seeking mental health among Saudi Arabians - Alissa, Nawal A. (J Educ Health Promot, 2021)
BACKGROUND: To extend our knowledge of social barriers in relation to mental health, the present study was conducted to investigate the impact of social barriers on mental health help-seeking among Saudi Arabians aged 18 years and above. MATERIALS AND METHODS: This cross-sectional study was carried out on 1632 participants in 2018 during the months of October and November. The participants completed self-administered online surveys about the demographic characteristics, social barriers, and knowledge and attitudes about mental health. RESULTS: The majority of the participants agreed that social barriers could prevent them from seeking mental health help. Stigma was chosen as the most common social barrier among the participants (76.3%), followed by culture (61.5%) and negative perceptions (56.2%). CONCLUSION: Social barriers are a challenge in seeking mental health. Increasing public awareness of available services and resources as well as developing programs to fight stigmatization should be initiated to create more positive attitudes toward people with mental illness and promote holistic well-being.